Metadata - Phrases and total song detections - Magnusdottir, Edda E.; Lim, Rangyn (Dryad Digital Repository, 2019)
The spread sheet contains 4 different datasets each located in a separate sheet. The first sheet contains all the acoustic sound files detected with the automatic humpback whale song detector ("All_detections"). In the second sheet named "Phrases" there is a subsample of humpback whale song files which was created from the whole dataset. This subsample was used to analyse phrase occurrence and sequences of phrases. The third sheet named "AnalysedSoundFiles_subsample" contains a random subsample of sound files from the sheet "Phrases". This subsample was used to measure the average signal to noise ratio of the song units in the sound files, including the average received signal level to investigate differences in these values in analysed sound files between periods within the total study period. The forth sheet named "TotalFiles_Randosubsample" contains a random subsample of the total detected files from the sheet "All_detections". That data was used to investigate the effect of different received signal levels and SNR on the automatic acoustic detector.